Солитоны Рассела в цилиндрической пружине - Ванин, Виктор Антонович; Григорьев, А. А. (НТУ "ХПИ", 2009)
Показано, що низькочастотні нелінійні коливання циліндричної пружини описуються рівняннями Кортевега- де Фриза. Отримані формули, що пов’язують амплітуду, енергію та імпульс солітона зі швидкістю його руху по гвинтовому стрижню.

It is shown, that the low-frequency non-linear oscillations of the cylindrical spring have been described by the equations of Korteveg-de Vries. The formulae relating the amplitude, the energy and the pulse of the soliton with its traveling Speed along the spiral rod have been gained.
Keywords: нелинейные колебания; уравнение Кортевега-де Фриза; продольные колебания; поперечные колебания